India: MANAGE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
MANAGE, the National Institute of Agricultural Extension Management, an agency of the Ministry of Agriculture, is a unique programme to take better farming methods to farmers across the country. The MANAGE website is a portal to a wide range of services,